TAS2R16 Activation Suppresses LPS-Induced Cytokine Expression in Human Gingival Fibroblasts - Zhou, Zhiyan; Xi, Ranhui; Liu, Jiaxin; Peng, Xian; Zhao, Lei; Zhou, Xuedong; Li, Jiyao; Zheng, Xin; Xu, Xin (Frontiers in Immunology, 2021)
Sustained and non-resolved inflammation is a characteristic of periodontitis. Upon acute inflammation, gingival fibroblasts release cytokines to recruit immune cells to counter environmental stimuli. The intricate regulation of pro-inflammatory signaling pathways, such as NF-κB, is necessary to maintain periodontal homeostasis. Nonetheless, how inflammation is resolved has not yet been elucidated. In this study, 22 subtypes of taste receptor family 2 (TAS2Rs), as well as the downstream machineries of Gα-gustducin and phospholipase C-β2 (PLCβ2), were identified in human gingival fibroblasts (HGFs). Various bitter agonists could induce an intensive cytosolic Ca2+ response in HGFs. More importantly, TAS2R16 was expressed at a relatively high level, and its agonist, salicin, showed robust Ca2+ evocative effects in HGFs. Activation of TAS2R16 signaling by salicin inhibited the release of lipopolysaccharide (LPS)-induced pro-inflammatory cytokines, at least in part, by repressing LPS-induced intracellular cAMP elevation and NF-κB p65 nuclear translocation in HGFs. These findings indicate that TAS2Rs activation in HGFs may mediate endogenous pro-inflammation resolution by antagonizing NF-κB signaling, providing a novel paradigm and treatment target for the better management of periodontitis.